PROGRAM KEMITRAAN MASYARAKAT PEMBUATAN GULA SEMUT DI DESA LONUO - Larosa, Esta; Saputra, Wahyu; MUTMAINNAH, NUR (Jurnal Abdimas Terapan, 2024)
Desa Lonuo, located in the Tilongkabila District of Bone Bolango Regency, Gorontalo, has significant potential in the development of palm sugar as a flagship product. The main challenges faced by the community include a lack of technology and effective marketing methods, as well as limitations in developing derivative products. The objectives of this community service initiative are to enhance knowledge and skills, improve the quality and quantity of production, develop marketing methods, and diversify products. The method used is community collaboration, which involves cooperation between the community and external institutions to achieve shared goals. This initiative has received enthusiastic support and participation from the village government and partners. Several improvements have been noted, including the processing of palm sugar without chemical additives or preservatives. Additionally, the production of palm sugar using modern drying machines has been implemented in Desa Lonuo to enhance quality and quantity. Furthermore, this product is expected to serve as an attractive ingredient in various foods and beverages. The packaging and design of palm sugar products from Desa Lonuo are also anticipated to attract buyers, thereby improving the economic situation of local palm sugar farmers. Lastly, the initiative supports government programs aimed at food diversification by utilizing high-quality local food ingredients.